Expression of Components of the Renin-Angiotensin System by the Embryonic Stem Cell–Like Population within Keloid Lesions. Issue 2 (August 2019) - Humphries, Hugo; Brasch, Helen D.; van Schaijik, Bede; Tan, Swee T.; Itinteang, Tinte
Abstract : Background: We investigated expression of prorenin receptor, angiotensin-converting enzyme, angiotensin II receptor 1, and angiotensin II receptor 2 by the embryonic stem cell-like population on the endothelium of the microvessels and perivascular cells within keloid-associated lymphoid tissues. Methods: Immunohistochemical staining for prorenin receptor, angiotensin-converting enzyme, angiotensin II receptor 1, and angiotensin II receptor 2 was performed on 11 formalin-fixed, paraffin-embedded sections of keloid tissue samples. Immunofluorescence staining was performed on three keloid tissue samples by co-staining with OCT4, CD34, ERG, and tryptase. Real-time quantitative polymerase chain reaction was performed on five keloid tissue samples and four keloid-derived primary cell lines. Western blotting was performed on the four keloid-derived primary cell lines for mRNA and protein expression of these proteins, respectively. Results: Immunohistochemical and immunofluorescence staining showed expression of prorenin receptor, angiotensin-converting enzyme, angiotensin II receptor 1, and angiotensin II receptor 2 in all 11 keloid tissue samples. Prorenin receptor and angiotensin II receptor 1 were expressed on the endothelium and the pericyte layer of the microvessels and perivascular cells, angiotensin II receptor 2 was localized to the endothelium of the microvessels and the tryptase-positive perivascular cells, and angiotensin-converting enzyme was localized to the endothelium of the microvessel, within the keloid-associated lymphoid tissues. Real-time quantitative polymerase chain reaction showed transcripts of prorenin receptor, angiotensin-converting enzyme, and angiotensin II receptor 1 in the keloid tissue samples and keloid-derived primary cell lines, whereas angiotensin II receptor 2 was detected in keloid tissue samples only. Western blotting confirmed the presence of prorenin receptor, angiotensin-converting enzyme, and angiotensin II receptor 1 in the keloid-derived primary cell lines. Conclusion: Prorenin receptor, angiotensin-converting enzyme, angiotensin II receptor 1, and angiotensin II receptor 2 were expressed by the embryonic stem cell–like population within the keloid-associated lymphoid tissues, suggesting that this primitive population may be a potential therapeutic target by modulation of the renin-angiotensin system. Abstract : Supplemental Digital Content is available in the text.